Comparative study of overall dimensions and arranging of classroom desks with different shapes of worksurfaces - Kosenko, D. (Theory and practice of design, 2017)
Collaborative school desks with non-rectangular worksurfaces are studied from the point of room area needed. Found that both trapezoid and petal-shaped desks should be bigger in overall dimensions comparing to rectangular desks to meet the needs of academic work. Equipping classrooms with collaborative desks needs more room space while arranging desks either in rows or in groups.